The two faces of justice - Ci, Jiwei, 1955- (Harvard University Press, 2006)
Justice is a human virtue that is at once unconditional and conditional. Under favorable circumstances, we can be motivated to act justly by the belief that we must live up to what justice requires, irrespective of whether we benefit from doing so. But our will to act justly is subject to conditions. We find it difficult to exercise the virtue of justice when others regularly fail to. Even if we appear to have overcome the difficulty, our reluctance often betrays itself in certain moral emotions. In this book, Jiwei Ci explores the dual nature of justice, in an attempt to make unitary sense of key features of justice reflected in its close relation to resentment, punishment, and forgiveness. Rather than pursue a search for normative principles, he probes the human psychology of justice to understand what motivates moral agents who seek to behave justly, and why their desire to be just is as precarious as it is uplifting. A wide-ranging treatment of enduring questions, The Two Faces of Justice can also be read as a remarkably discerning contribution to the Western discourse on justice re-launched in our time by John Rawls.